PEMANFAATAN SAMPAH DAUN SEBAGAI BAHAN CAMPURAN PAPAN PANEL SEMEN DENGAN BAHAN IKAT MU PLESTERAN - Anni Susilowati (Politeknik Negeri Jakarta, 2012)
This research was conducted on cement board panel using Glodogan leaves, that were already cut into pieces with a length of 5-20 mm and a width of 3-10 mm. Then, they were soaked in cold water for 24 hours than dried in room temperature for a day. Various compositions used for the mixture of instant cement volume MU-301 and leaf waste were 1: 0, 1: 0.2, 1: 0.4, 1: 0.6, 1: 0.8, and 1: 1.0 with a water mixture ratio of 0.15. The process of making the mixture was done by using a vibrating table of 30-60 seconds and then carried out hydraulic compression with a load of 3 kg/cm ². The result indicates that more leaf waste in cement board panel leads to an increased water seepage, water absorption, moisture content and thickness swelling. Moreover, increasing the addition of leaf waste can also reduce the density, specific gravity, flexural strength, compressive strength and tensile strength. The result also indicates that the lowest the highest flexural strength of 2.90 MPa does not meet the minimum requirement of 10 MPa (SNI 15-0233-1989), which was resulted from the mixture with the composition of leaf waste 0.2. This was the most possible mixture to be developed. Keywords: Leaves waste, cement board panel, flexural strength, water absorption, and water seepage. Abstrak. Penelitian dilakukan pada papan panel semen dengan menggunakan daun Glodogan dipotong-potong ukuran panjang 5 - 20 mm dan lebar 3 - 10 mm kemudian direndam dalam air dingin selama 24 jam dan dikeringkan. Komposisi campuran yang digunakan berdasarkan perbandingan volume campuran semen instan MU-301 : SD adalah 1 : 0; 1 : 0,2; 1 : 0,4; 1 : 0,6 ; 1 : 0,8; 1 : 1,0 dengan faktor air campuran (f.a.c.) 0,15. Proses pembuatan dilakukan dengan penggetaran menggunakan vibrating table selama 30 - 60 detik kemudian dilakukan pengempaan hidraulis dengan beban sebesar 3 kg/cm². Hasil analisis menunjukkan semakin banyak sampah daun pada papan panel semen mengakibatkan peningkatan rembesan air, daya serap air, kadar air dan pengembangan tebal. Selain meningkatkan penambahan sampah daun juga dapat menurunkan densitas, berat jenis, kuat lentur, kuat tekan dan kuat tarik. Hasil penelitian kuat lentur tertinggi sebesar 2,90 MPa tidak memenuhi persyaratan minimum 10 MPa (SNI 15-0233-1989), yang dihasilkan oleh campuran dengan komposisi variasi 0,2 SD. Campuran ini merupakan campuran yang paling memungkinkan untuk dikembanngkan. Kata kunci : Sampah daun, papan panel semen, kuat lentur, daya serap air, rembesan air